Fatigue Is Associated With Diminished Cardiovascular Response to Anticipatory Stress in Patients With Coronary Artery Disease - Gecaite-Stonciene, Julija; Hughes, Brian M.; Burkauskas, Julius; Bunevicius, Adomas; Kazukauskiene, Nijole; van Houtum, Lisanne; Brozaitiene, Julija; Neverauskas, Julius; Mickuviene, Narseta (Frontiers in Physiology, 2021)
Background. Fatigue and psychophysiological reactions to mental stress are known to be problematic in coronary artery disease (CAD) patients. Currently, studies exploring the relationship between fatigue and cardiovascular reactivity to stress are scarce and inconsistent. The current study aimed to investigate the links between cardiovascular response to mental stress and fatigue in CAD patients after acute coronary syndrome (ACS). Methods. The cross-sectional study investigated 142 CAD patients (85% males, 52±8 years) within 2-3 weeks after recent myocardial infarction or unstable angina pectoris. Fatigue symptoms were measured using Multidimensional Fatigue Inventory 20-items, while cardiovascular reactivity to stress (i.e. systolic [S] and diastolic [D] blood pressure [ΔBP], and heart rate [ΔHR]) was evaluated during Trier Social Stress Test (TSST). In addition, participants completed psychometric measures, including the Hospital Anxiety and Depression scale and the Type D Scale-14. Multivariable linear regression analyses were completed to evaluate associations between fatigue and cardiovascular response to TSST, while controlling for confounders. Results. After controlling for baseline levels of cardiovascular measures, age, gender, education, heart failure severity, arterial hypertension, smoking history, use of nitrates, anxiety and depressive symptoms, Type D Personality, perceived task difficulty, and perceived task efforts, cardiovascular reactivity to anticipatory stress was inversely associated with both global fatigue (ΔHR: β=-0.238; p=0.04) and mental fatigue (ΔSBP: β=-0.244; p=0.04; ΔHR β=-0.303; p=0.01) as well as total fatigue (ΔSBP: β=-0.331; p=0.01; ΔHR: β=-0.324; p=0.01). Conclusions: In CAD patients after ACS, fatigue was linked with diminished cardiovascular function during anticipation of a mental stress challenge, even after inclusion of possible confounders. Further similar studies exploring other psychophysiological stress responses are warranted.